2018
DOI: 10.1155/2018/9125746
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Superficial Acupuncture in Treating Myofascial Pain of the Upper Trapezius Muscle: A Randomized Controlled Trial

Abstract: The aim of this study was to compare the treatment efficacies of superficial acupuncture and traditional acupuncture on trigger points of the upper trapezius muscle. Forty people were recruited and randomly allocated to the traditional and superficial acupuncture groups. Each subject received two treatments per week in a four-week period. Outcomes were measured by visual analogue scale (VAS), the Northwick Park neck pain questionnaire scores (NPQ), and pressure pain threshold (PPT) assessments of trigger point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…DN has demonstrated mechanical, biochemical, vascular and neurophysiological effects [7][8][9][10][19][20][21][22][23][24][25][26][27][28][29][30]. Studies identified DN to be an effective technique to reduce pain, disability, and range of motion (ROM) deficits, while increasing pain pressure thresholds (PPT) [13,23,29,[31][32][33][34][35][36][37][38][39][40][41] In a randomized trial of 65 subjects with nonspecific low back pain, Griswold et al [33] compared segmental and distal DN without needle manipulation to non-thrust manipulation (NTM) after 6 sessions over 3 weeks. Outcome measures were the Owestry Disability Index (ODI), Patient Specific Functional Scale (PSFS), Numerical Pain Rating Scale (NPRS), and PPT.…”
Section: Introductionmentioning
confidence: 99%
“…DN has demonstrated mechanical, biochemical, vascular and neurophysiological effects [7][8][9][10][19][20][21][22][23][24][25][26][27][28][29][30]. Studies identified DN to be an effective technique to reduce pain, disability, and range of motion (ROM) deficits, while increasing pain pressure thresholds (PPT) [13,23,29,[31][32][33][34][35][36][37][38][39][40][41] In a randomized trial of 65 subjects with nonspecific low back pain, Griswold et al [33] compared segmental and distal DN without needle manipulation to non-thrust manipulation (NTM) after 6 sessions over 3 weeks. Outcome measures were the Owestry Disability Index (ODI), Patient Specific Functional Scale (PSFS), Numerical Pain Rating Scale (NPRS), and PPT.…”
Section: Introductionmentioning
confidence: 99%
“…This could involve slight anaesthesia, heat, sight pain, electrical current or tension sensation at the point where the needle is inserted(50). However, the Teh Chi, although it is connected to the effectiveness of acupuncture, it is not always required for it and many practitioners do not try to obtain that as it requires mainly deeper acupuncture, which could be more painful and connected with more complications as well (51).…”
Section: Acupuncture Theoriesmentioning
confidence: 99%
“…One of the eminent acupuncture practitioners of that time Dou Han Qing organised and documented the various needling techniques and suggested many ways with the aim to eliminate the discomfort and increase the speed of needle insertion at the same time (38). Other practitioners of acupuncture focused on the improvement of the sterilisation process, as only recently single use sterile needles were introduced for acupuncture, while other dealt mainly with the complications, such as broken needles( 38) (51). The acupuncture needles made of steel, still in use in our days, developed later probably during the 18 th to 19 th century.…”
Section: Acupuncture Techniquementioning
confidence: 99%
See 2 more Smart Citations